Cutaneous Vasoconstriction during Whole-Body and Local Cooling in Grafted Skin Five to Nine Months Postsurgery - Davis, Scott L. (2008)
The aim of this investigation was to test the hypothesis that skin grafting (5–9 months after surgery) impairs sympathetically mediated cutaneous vasoconstrictor responsiveness. Skin blood flow (laser-Doppler flowmetry) was assessed in grafted skin and adjacent healthy control skin in fourteen subjects (seven male, seven female) during indirect whole-body cooling (ie, cooling the entire body, except the area where skin blood flow was assessed), as well as local cooling (ie, only cooling the area where skin blood flow was assessed). Whole-body cooling was performed by perfusing 5°C water through a water perfusion suit for 3 minutes. Local cooling was performed on a separate visit using a custom Peltier cooling device, which decreased local skin temperature from 39 °C to 19 in 5 °C decrements in 15-minute stages. Cutaneous vascular conductance (CVC) was calculated from the ratio of skin blood flow to mean arterial pressure. Indirect whole-body cooling decreased CVC from baseline (ΔCVC) similarly (P = 0.17) between grafted skin (ΔCVC = −0.23 ± 0.04 au/mm Hg) and adjacent healthy skin (ΔCVC = −0.16 ± 0.02 au/mm Hg). Likewise, decreasing local skin temperature from 39 to 19 °C resulted in similar decreases (P = .82) in CVC between grafted skin (ΔCVC = −1.11 ± 0.18 au/mm Hg) and adjacent healthy skin (ΔCVC = −1.06 ± 0.18 au/mm Hg). Appropriate cutaneous vasoconstriction in grafted skin to both indirect whole-body and local cooling indicates re-innervation of the cutaneous vasoconstrictor system at the graft site. These data suggest that persons with significant skin grafting may have a normal capacity to regulate body temperature during cold exposure by cutaneous vasoconstriction.